2021
DOI: 10.1088/1758-5090/abfd7a
|View full text |Cite
|
Sign up to set email alerts
|

Combinations of photoinitiator and UV absorber for cell-based digital light processing (DLP) bioprinting

Abstract: Digital light processing (DLP) bioprinting, which provides predominant speed, resolution, and adaptability for fabricating complex cell-laden three-dimensional (3D) structures, requires a combination of photoinitiator (PI) and UV absorber (UA) that plays critical roles during the photo-polymerization of bioinks. However, the PI and UA combination has not been highlighted for cell-based DLP bioprinting. In this study, the most used PIs and UAs in cell-based bioprinting were compared to optimize a combination th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 51 publications
1
68
1
Order By: Relevance
“…[12] Ponceau 4R (red food dye) was studied by Lim et al [44] demonstrated that addition of 1 wt% of the absorber was suitable for a poly(vinyl alcohol)-methacrylate (PVA-MA) resin, allowing improved control over print resolution. Other widely used photoabsorbers are 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid (HMBS) [172,175,176] and TINUVIN 234. [174] HMBS is an attractive photoabsorber used in biomedical applications as it is an FDA approved chemical used in sunscreen and cosmetic products.…”
Section: Photoabsorbing Dyes and Pigmentsmentioning
confidence: 99%
“…[12] Ponceau 4R (red food dye) was studied by Lim et al [44] demonstrated that addition of 1 wt% of the absorber was suitable for a poly(vinyl alcohol)-methacrylate (PVA-MA) resin, allowing improved control over print resolution. Other widely used photoabsorbers are 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid (HMBS) [172,175,176] and TINUVIN 234. [174] HMBS is an attractive photoabsorber used in biomedical applications as it is an FDA approved chemical used in sunscreen and cosmetic products.…”
Section: Photoabsorbing Dyes and Pigmentsmentioning
confidence: 99%
“…Digital light processing bioprinting technology has enhanced the resolution (~10 times) of bioprinted PDOs, which has been one notable barrier with nozzle extrusion ( 159 162 ). In addition, digital light processing bioprinting offers a shear stress–free advantage over extrusion bioprinting by reducing potential cell damage during organotypic assembly ( 66 , 158 , 162 ). This shear stress–free printing method achieves a cell viability of ≥90% within the 3D-printed construct, whereas that of extrusion bioprinting is 40%–80% ( 66 ).…”
Section: Overcoming the Fabrication Complexity Of Patient-derived Org...mentioning
confidence: 99%
“…When a photoinitiator is exposed to the light energy of a reactive wavelength, it generates free radicals that initiate photopolymerization with the polymer in the bioink [ 16 , 17 ]. However, LAP is suited for the absorption of UV and blue-light wavelengths (350–400 nm); the UV absorption range has been known to negatively affect cell behavior and generate excessive heat [ 18 , 19 ]. In addition, the relatively wide absorption wavelengths of bioinks are often incompatible with the wavelength band of the commercially available printer projection light; this may affect printability.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, excessive light exposure energy causes light to penetrate beyond the focal layer, resulting in over-crosslinking, which leads to an undesired shape. Recently, a multi-hollow channel test was employed to assess over-crosslinking in DLP bioprinting [ 19 ]. However, to calculate the optimal amount of exposure energy in this method, a trial-and-error process, comprising the modification of light exposure energy for different condition values, is essential.…”
Section: Introductionmentioning
confidence: 99%